Multidimensional Analysis of Community Vulnerability to Flood Risks in West Jakarta - Devinta Dwi Insani; Juhadi Juhadi (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the level and determinants of multidimensional community vulnerability to flooding in West Jakarta, an area with high exposure to flood risk due to natural and anthropogenic factors. The analysis is based on four main dimensions: social, economic, physical, and environmental, using a quantitative descriptive approach. The assessment method refers to BNPB Number 2 of 2012 through weighting and scoring techniques. Data was obtained from field observations, questionnaire surveys, in-depth interviews, and documentation studies from relevant agencies. The results of the study show that Tambora Subdistrict has the highest vulnerability score compared to other subdistricts. Social vulnerability is characterized by high population density and the dominance of vulnerable groups such as children and the elderly. The economic aspect reflects the community's dependence on the informal sector and the limited availability of productive assets. Physical vulnerability is evident in the presence of vital infrastructure in flood-prone zones. Meanwhile, the environmental aspect highlights a significant contribution to vulnerability due to the scarcity of green open spaces and the area's low absorption capacity. The findings of this study underscore the necessity of enhancing both structural and non-structural capacities via cross-sectoral collaboration in adaptive, contextual, and evidence-based planning for disaster risk reduction.